-1
$\begingroup$

Let $y(t)=s(t)+n(t)$

For the matched filter h(t) on $[0,T]$ we have, $h(t)=s(T-t)$. And the output is: $z(t)=\int_0^T y(u)h(t-u)du=\int_0^T y(u)s(t-(T-u))du=\int_0^T y(u)s(u-(T-t))du$

But sometimes I see, $z(t)=\int_0^T y(u)s(u)du$. How do we get the last equation?

$\endgroup$
  • 1
    $\begingroup$ $t=T$ the convolution is at its maximum value $\endgroup$ – Stanley Pawlukiewicz May 6 '18 at 13:35
2
$\begingroup$

$z(t)$ cannot possibly equal $\displaystyle \int_0^T y(u)s(u) \mathrm du$ unless $z(t)$ has constant value for all $t$: the value of the integral does not depend on $t$ at all! Nor is your convolution integral correct. If $s(t)$ is nonzero only for $t \in [0,T]$, then so is $h(t) = s(T-t)$ nonzero only for $t \in [0,T]$. Consequently, for every real number $t, -\infty < t < \infty$, the matched filter output $z(t)$ is given by \begin{align} z(t) &= \int_{-\infty}^\infty y(u)h(t-u) \,\mathrm du\\ &= \int_{t-T}^t y(u)h(t-u) \,\mathrm du &{h(t-u) = 0~ \text{whenever}~u >t~\text{or}~ u < T-t}\\ &= \int_{t-T}^t y(u)s(u+(T-t)) \,\mathrm du\\ &= \int_{0}^T y(v+T-t)s(v) \,\mathrm dv.\tag{1} \end{align} Now, when $t$ equals $T$, we get that the matched filter output at time $t=T$ is $$z(T) = \int_{0}^T y(v)s(v) \,\mathrm dv = \int_{0}^T y(u)s(u) \,\mathrm du.\tag{2}$$ Note clearly the difference between your $\displaystyle z(t) = \int_0^T y(u)s(u) \mathrm du$ and what you (or your textbook author) should have written, namely $(2)$.

As @Stanley Pawlukiewicz points out, the matched filter output has a maximum value at $t=T$. For this result, (and far more than you probably want to know about matched filters), see this answer of mine on this site.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.